APPLICATION OF GUIDED DISCOVERY LEARNING MODEL HELPED AUTOGRAPH SOFTWARE - ticaya, ticaya (Jurnal Pengajaran MIPA, 2018)
Students have not been able to find the concept independently in analyzing the graph of trigonometric functions. The purpose of this study was to determine the improvement of student learning outcomes with guided discovery learning models assisted by Autograph Software on trigonometric function graphics material at SMA Negeri 1 Lhoknga, Aceh Besar. The research sample was students of class X IPA-1 as an experimental class who obtained learning with a guided discovery model assisted by Autograph Software and students of class X IPA-2 as a control class who obtained learning with guided discovery models without the help of Autograph Software. Based on the results of the study, it is known that the improvement of learning outcomes of students who get learning with guided discovery models assisted by Autograph Software is better than improving learning outcomes of students who get learning with guided discovery models without the help of Autograph Software.